How does foreign economic policy uncertainty affect domestic analyst earnings forecasts? - Song, Jian; Zhou, X. (2025)
This study examines the impact of foreign economic policy uncertainty (EPU) on the performance of domestic analyst earnings forecasts. We separately analyze how U.S. EPU affects the accuracy of analyst earnings forecasts in other markets and the reverse relationship. Our findings indicate that the U.S. EPU (non-U.S. Global EPU) negatively (positively) affects the accuracy of analyst earnings forecasts in other economies (the U.S.). We find that the economic dependency of a given economy on the U.S. (capital flow to the U.S.) is a channel for this negative (positive) impact. Our results remain robust after controlling for a comprehensive set of variables.